Echoes from beyond: detecting gravitational-wave quantum imprints with LISA - Deppe, Nils; Heisenberg, Lavinia; Inchauspé, Henri; Kidder, Lawrence E.; Maibach, David; Ma, Sizheng; Moxon, Jordan; Nelli, Kyle C.; Throwe, William; Vu, Nils L. (Physical review, 2025)
We revisit gravitational wave echoes as a pathway to measuring quantization effects of black hole horizons. In particular, we construct a robust and phenomenologically motivated toy model for black hole reflectivity, enabling us to estimate the detectability of waveform echoes in gravitational wave interferometer data. We demonstrate how the frequency information of echoes, upon detection, can be leveraged to probe and constrain the quantum scale associated with the underlying theory of quantum gravity. Our analysis shows that echoes may manifest in LISA data with an estimated signal-to-noise ratio of up to 𝒪⁡(102). For such signals, the frequency features indicative of horizon quantization can be determined with subpercent precision.
Gesehen am 09.12.2025